Socioeconomic profile of the Brazilian fishermen - Gomes de Alencar, Carlos Alexandre; Maia, Luis Parente (Arquivos de Ciências do Mar, 2011)
This paper analyzes the General Database for Fishery Activities (RGP) of the Ministry of Fisheries and Aquaculture, considering the region, production, average income, gender, age and education. In 2008 there were 693,705 registered fishermen in the RGP system, distributed in 60.6% of Brazilian municipalities. The Northeastern and Northern regions have the highest number, representing 77.0% of the fishermen, followed respectively by the Southeast, South and Midwest regions. The Northern region leads the national fish production, with 233,534 tons, followed by the Northeast (222,671 tons), South (171,291 tons), Southeast (141,281 tons) and Midwest (10,335 tons). Fishermen of South and Southeast regions are more productive, with average catch of 2.61 ton/fisherman/ year and 1.83 ton/fisherman/year, respectively, which leads to higher values of average annual income. As for gender distribution, 34.9% of fishermen are women. Regarding education, Brazil has 56,218 illiterate fishermen and 523,841 have incomplete elementary school, which is a major part of Brazilian fishermen (83.6%). The low education level may be responsible for the inefficiency in the implementation of fisheries policies, and it is also related to the easy access of people into this activity, thus fueling the paradigm of fisheries to poverty